Pentingnya Kepercayaan Diri Dalam Meningkatkan Minat Belajar Anak Di Rumah Pintar YAFSI - Nurul Fadillah Nasution; Husni Thamrin (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Self-confidence is an important indicator for self-development in success. Self-confidence is one of the factors that influence the high and low learning outcomes of children. A child who does not dare to show his interest and ability in learning will always be left behind in the lesson because he continues to feel hesitant to show it. In this case, it is important to cultivate a sense of self-confidence in the child in order to further increase the child's interest in learning. Various efforts were made to increase self-confidence in children, including YAFSI Smart Home children. Through the Practicum 1 activity which will start from March to June 2022, the author conducted a mini project on one of the YAFSI Smart Home children. In this Practicum, the method used is the Casework Method by Zastrow which includes Intake Contract, Assessment, Planning, Intervention, Evaluation and Termination. The tools used in the assessment are ecomap tools that help find the source of the problem in the client. The efforts made in this Practicum make clients feel an increased interest in learning because of their self-confidence. Because, the interests that children have will make them interested and happy with something they learn